ДУНД-ХОЖУУ ЮРИЙН “АРАГ” ГРАНИТЫН МАССИВЫН ГЕОХИМИЙН СУДАЛГАА БА ХҮДЭРЖИЛТ - Д.ОЮУНЦЭЦЭГ; Д.БАТ-ӨЛЗИЙ (Geological Issues, 2023)
ДУНД-ХОЖУУ ЮРИЙН “АРАГ” ГРАНИТЫН МАССИВЫН ГЕОХИМИЙН СУДАЛГАА БА ХҮДЭРЖИЛТ